STAT1-mediated Bim expression promotes the apoptosis of retinal pericytes under high glucose conditions - Shin, E S (Nature Publishing Group, 2014)
Hyperglycemia impacts different vascular cell functions and promotes the development and progression of various vasculopathies including diabetic retinopathy. Although the increased rate of apoptosis in pericytes (PCs) has been linked to increased oxidative stress and activation of protein kinase C-δ (PKC-δ) and SHP-1 (Src homology region 2 domain-containing phosphatase-1) tyrosine phosphatase during diabetes, the detailed mechanisms require further elucidation. Here we show that the rate of apoptosis and expression of proapoptotic protein Bim were increased in the retinal PCs of diabetic Akita/+ mice and mouse retinal PCs cultured under high glucose conditions. Increased Bim expression in retinal PCs under high glucose conditions required the sustained activation of signal transducer and activator of transcription 1 (STAT1) through production of inflammatory cytokines. PCs cultured under high glucose conditions also exhibited increased oxidative stress and diminished migration. Inhibition of oxidative stress, PKC-δ or Rho-associated protein kinase I/II was sufficient to protect PCs against apoptosis under high glucose conditions. Furthermore, PCs deficient in Bim expression were protected from high glucose-mediated increased oxidative stress and apoptosis. However, only inhibition of PKC-δ lowered Bim levels. N-acetylcysteine did not affect STAT1 levels, suggesting that oxidative stress is downstream of Bim. PCs cultured under high glucose conditions disrupted capillary morphogenesis of retinal endothelial cells (ECs) in coculture experiments. In addition, conditioned medium prepared from PCs under high glucose conditions attenuated EC migration. Taken together, our results indicate that Bim has a pivotal role in the dysfunction of retinal PCs under high glucose conditions by increasing oxidative stress and death of PCs.